Hubungan Lingkungan Pengasuhan dan Pekerjaan Ibu terhadap Perkembangan Bayi 6-12 Bulan - Herlina, Sara (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Indonesia Health Demographic Survey (SDKI) Survey in 2012 shows the number of children aged (0 to 6 years) as much as 26.1 million, about 14.1 percent of the number of children experiencing developmental delays. There are several factors that influence the babys development such as parents curvature and mothers work. The purpose of this research is to know the relation of mothering environment and mothers work to baby development. The design of this study was cross sectional with a large sample of 151 people. Sampling method used systematically random sampling. The data were analyzed by univariate, bivariate and multivariate. The results of the study were given by the majority of good parenting environment as much as 39.7 percent, mothers did not work as much as 60.9 percent, and the baby had normal development as much as 52.3 percent. The result of chi square test of relationship between parenting environment to infant development obtained value of Pvalue less than 0,005 that is less than 0,000 relation between mother job to infant development obtained value of Pvalue less than 0,005 that is 0,003. So it can be concluded that there is a relationship between the parenting environment and the mothers work on infant development. Keywords: parenting environment, mothers work, development